2019
DOI: 10.1002/ejhf.1664
|View full text |Cite
|
Sign up to set email alerts
|

Baseline features of the VICTORIA (Vericiguat Global Study in Subjects with Heart Failure with Reduced Ejection Fraction) trial

Abstract: AimDescribe the distinguishing features of heart failure (HF) patients with reduced ejection fraction (HFrEF) in the VICTORIA (Vericiguat Global Study in Patients with Heart Failure with Reduced Ejection Fraction) trial.Methods and resultsKey background characteristics were evaluated in 5050 patients randomized in VICTORIA and categorized into three cohorts reflecting their index worsening HF event. Differences within the VICTORIA population were assessed and compared with PARADIGM‐HF (Prospective comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 14 publications
0
46
0
1
Order By: Relevance
“…Baseline characteristics of VICTORIA‐enrolled subjects showed a high‐risk population when compared with PARADIGM‐HF. The median MAGGIC (Meta‐Analysis Global Group in Chronic Heart Failure) risk score was 23 (interquartile range 18–27) in VICTORIA vs. 20 (interquartile range 16–24) in PARADIGM‐HF trial 198 . In the GALACTIC‐HF (Global Approach to Lowering Adverse Cardiac outcomes Through Improving Contractility in Heart Failure) trial, the selective cardiac myosin activator omecamtiv mecarbil showed a reduction in the primary composite endpoint of a first HF event or death from CV causes 199 …”
Section: Medical Treatment Of Heart Failure With Reduced Ejection Framentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline characteristics of VICTORIA‐enrolled subjects showed a high‐risk population when compared with PARADIGM‐HF. The median MAGGIC (Meta‐Analysis Global Group in Chronic Heart Failure) risk score was 23 (interquartile range 18–27) in VICTORIA vs. 20 (interquartile range 16–24) in PARADIGM‐HF trial 198 . In the GALACTIC‐HF (Global Approach to Lowering Adverse Cardiac outcomes Through Improving Contractility in Heart Failure) trial, the selective cardiac myosin activator omecamtiv mecarbil showed a reduction in the primary composite endpoint of a first HF event or death from CV causes 199 …”
Section: Medical Treatment Of Heart Failure With Reduced Ejection Framentioning
confidence: 99%
“…The median MAGGIC (Meta-Analysis Global Group in Chronic Heart Failure) risk score was 23 (interquartile range 18-27) in VICTORIA vs. 20 (interquartile range 16-24) in PARADIGM-HF trial. 198 In the GALAC-TIC-HF (Global Approach to Lowering Adverse Cardiac outcomes Through Improving Contractility in Heart Failure) trial, the selective cardiac myosin activator omecamtiv mecarbil showed a reduction in the primary composite endpoint of a first HF event or death from CV causes. 199 Neladenoson bialanate, a partial adenosine A1 receptor agonist, failed to demonstrate favourable changes in NT-proBNP, LVEF, high-sensitivity troponin T, or CV mortality and HF hospitalization in PANTHEON trial.…”
Section: Other Optionsmentioning
confidence: 99%
“…Aktivator solubilne guanilat ciklaze (sGC) vericiguat istraživan je u studiji VICTORIA na 5050 bolesnika s nedavnom dekompenziranom fazom kroničnog HF i LVEF <45%. 125,126 Vericiguat znatno smanjuje primarni ishod od CV smrti ili prve hospitalizacije zbog HF-a (HR, 0,90; 95 % CI, 0,82 -0,98; P = 0,002). Dok vericiguat signifikantno smanjuje hospitalizacije zbog HF-a (HR, 0,90; 95 % CI, 0,81 -1 ,00), CV smrtnost se nije znatnije smanjila.…”
Section: Aktivator Solubilne Guanilat Ciklaze (Studije Victoria Vitaunclassified
“…[1][2][3][4][5] The latest of these, soluble guanylate cyclase (sGC) stimulation, was investigated in the large well-conducted, Vericiguat Global Study in Subjects with Heart Failure with Reduced Ejection Fraction trial (VICTORIA). 4,6,7 This new therapeutic approach is based on the hypothesis that the nitric oxide-sGC-cyclic guanosine monophosphate (cGMP) pathway is downregulated in heart failure and that its stimulation might be beneficial. 4,6,7 VICTORIA was quite different in design than in other recent HFrEF trials as shown in Tables 1 and 2.…”
mentioning
confidence: 99%
“…4,6,7 This new therapeutic approach is based on the hypothesis that the nitric oxide-sGC-cyclic guanosine monophosphate (cGMP) pathway is downregulated in heart failure and that its stimulation might be beneficial. 4,6,7 VICTORIA was quite different in design than in other recent HFrEF trials as shown in Tables 1 and 2. [8][9][10] In many respects, VICTORIA was more like prior 'acute' or 'hospitalized' heart failure trials, perhaps most closely resembling the Aliskiren Trial on Acute Heart Failure Outcomes (ASTRONAUT) in requiring both recent/current hospital admission (or equivalent) and an elevation of natriuretic peptide level.…”
mentioning
confidence: 99%